Atenção primária à saúde das pessoas com deficiências. - Queiroz, Isabelle Frota Ribeiro (2023)
Disability is recognized by the United Nations Convention on the Rights of Persons with Disabilities as an evolving concept, which results from the interaction between people with disabilities and behavioral and environmental barriers that prevent their full and effective participation in society on an equal basis. The growing demand for health information, especially in relation to people with disabilities, has increased the challenges inherent in its use to support decision-making, promotion of resources and public policies. Thus, the objective was to analyze how health information is recorded and monitored for people with disabilities within the scope of Primary Health Care. This is an exploratory and descriptive research with a qualitative approach, in which interviews were carried out. The field of investigation was the municipality of Sobral, whose locus for development was represented by the Family Health Centers at the headquarters and districts of the municipality. The study participants were 67 participants, being managers or health professionals who work in Primary Health Care. For data collection, semi-structured interviews were carried out with the help of guiding questions with these professionals. For data analysis, the Thematic Analysis Technique proposed by Bardin (2016) was used with the support of software R, version 4.1.1. Study approved by the Research Ethics Committee under Opinion number: 5,408,891. From then on, it was possible to analyze the responses of health professionals in five thematic classes, which highlight different situations of care for people with disabilities in PHC. In the category Knowledge of health professionals about disability, superficial knowledge on the topic is observed. Regarding the category Public policies aimed at people with disabilities, the lack of knowledge of the main policies by the professionals interviewed is noticeable. Regarding the identification and recording of health information for people with disabilities, it is clear that the identification of people with disabilities is carried out, in most cases, by Community Health Agents (CHA), with the recording of information being limited. to the CDS and Electronic Citizen Record (PEC) of the E-Sus system. It should be noted that there is no form or system nearby for recording this information. In relation to monitoring and referral flow in the Health Care Network (RAS), the practice still occurs, preferably in specialized care, which directly implies the search for quality health care for these people in PHC, as it becomes if necessary, the integrality and longitudinality of care. In the category The importance of health information for monitoring people with disabilities, although health professionals recognize the importance of information for comprehensive care, there is still a need to implement strategies aimed at improving records. Thus, care for people with disabilities proves, in practice, to be fragile and fragmented care, presenting significant limitations and with the need to implement a care model that meets the entirety of people with disabilities.